The generational gap: Mental disorder prevalence and disability amongst first and second generation immigrants in Australia. (December 2016) - Liddell, Belinda J.; Nickerson, Angela; Sartor, Lauren; Ivancic, Lorraine; Bryant, Richard A.
Abstract: Despite unprecedented numbers of migrants internationally, little is known about the mental health needs of immigrant groups residing in common countries of resettlement. The majority of studies support the 'healthy migrant hypothesis', but few studies have examined: 1) shifts in prevalence patterns across generations; 2) how prevalence relates to disability in immigrant groups. Our study examined the prevalence of common mental disorders and disability in first and second generation migrants to Australia. Twelve-month and lifetime prevalence rates of affective, anxiety, and substance use disorders were obtained from the Australian National Survey of Mental Health and Wellbeing (N = 8841). First generation immigrants (born overseas) and second generation immigrants (both parents overseas) from non-English and English speaking backgrounds were compared to an Australian-born cohort. Disability was indexed by days out of role and the WHO Disability Assessment Schedule (WHODAS12). First generation immigrants with non-English speaking (1G-NE) backgrounds evidenced reduced prevalence of common mental disorders relative to the Australian-born population (adjusted odds ratio 0.5 [95% CI 0.38–0.66]). This lower prevalence was not observed in second generation immigrant cohorts. While overall levels of disability were equal between all groups (p > 0.05), mental health-related disability was elevated in the 1G-NE group relative to the Australian-born group (p = 0.012). The findings challenge the overarching notion of the "healthy migrant" and suggest a dissociation between reduced prevalence and elevated mental health-related disability amongst first generation immigrants with non-English speaking backgrounds. These findings highlight the heterogeneous psychiatric needs of first and second generation immigrants.